Incidence of dental anxiety in young adults in relation to dental treatment experience - Thomson WM, Locker D, Poulton R (Blackwell Synergy, 2000)
To document the incidence of dental anxiety among individuals aged 18 years at baseline and 26 years at follow-up, and to determine if dental treatment experience continues to play a significant etiological role with respect to the onset of dental anxiety in young adults. Methods: Dental anxiety scale (DAS; Corah, 1969) scores at ages 15, 18 and 26 were obtained for Study members in the Dunedin Multidisciplinary Health and Development Study.